Platelets as Biomarkers of Coronary Artery Disease - Pasalic, Leonardo; Wang, Samuel S. Y.; Chen, Vivien M. Y. (Seminars in Thrombosis and Hemostasis, 2016)
Primary and secondary prevention of cardiovascular disease remain a public health priority. Effective risk stratification of patients is a central requisite for effective preventative care and several scoring systems incorporating biomarkers have been used for prognostication in patients to guide intervention decisions. Thrombosis of atherosclerotic coronary arteries is the main mechanism behind the acute coronary syndromes and since platelets play a pivotal role in the pathogenesis of thrombosis, atherogenesis, and angiogenesis, platelet-derived biomarkers are an attractive concept. This review assesses the potential and the limitations of a range of platelet-based assays as biomarkers for coronary artery disease.
Keywords: platelets; platelet function; biomarker; cardiovascular disease